Effect of thermal properties of a substrate on formation of self-arranged surface structures on evaporated polymer films. (September 2020) - Dombrovsky, Leonid A.; Frenkel, Mark; Legchenkova, Irina; Bormashenko, Edward
Highlights: Self-arranged surface structures on evaporated polymer film are studied. Experimental results for different substrates on the process are obtained. The suggested heat transfer model is in good agreement with experimental data. New results on suppression of the breath figures on the film are obtained. Abstract: It is confirmed experimentally that both the heat conduction along the substrate and its heat capacity affect significantly the self-organized structures on the surface of an evaporated polymer film. The analysis presented is based on a combination of the laboratory experiments and heat transfer modeling. It is shown that only a part of the holes on the film surface can be classified as the breath figures, whereas the others are formed due to the solvent evaporation in the film volume, under the solid surface crust of the film. A combined experimental and computational analysis enables the authors to obtain a convective instability of the boundary layer flow triggered by the fast evaporation of the solvent. Most likely, this effect is responsible for the large-scale surface pattern which looks as vertical strips of Bénard-like cells. The orifices grouped at the boundaries of these convective cells are definitely produced by the volume evaporation of solvent under the surface crust. The suppression of surface patterns with the use of metal-containing substrates is accompanied by more intense producing the porous structure inside the polymer film.